Robust Signature-Based Copyright Protection Scheme Using the Most Significant Gray-Scale Bits of the Image. (29th May 2012) - Awrangjeb, Mohammad
Abstract : The most significant bit - (MSB-) plane of an image is least likely to change by the most signal processing operations. This paper presents a novel multibit logo-based signature, using the most significant gray-scale bits, which is then used to develop an extremely simple but robust copyright protection scheme, where images along with their signatures are sent to a trusted third party when a dispute arises. Different ways of processing the MSB-plane before calculating the robust signature have been developed. This paper then presents an innovative classifier-based technique to test the robustness and uniqueness of any signature-based scheme. A new MSB-based attack, which would defeat our scheme most, has also been proposed. Experimental results have clearly demonstrated the superiority of the proposed scheme showing the high robustness of different MSB-based signatures over the existing signature-based schemes.